IN VITRO IMMUNE-MODULATORY POTENTIAL OF CRUDE EXTRACT OF LEAFS OF ALBIZIA GUMMIFERA AGAINST STIMULATED PERIPHERAL BLOOD MONONUCLEAR AND RAW CELLS - Makgatho, Marema Ephraim; Mashele, Aubrey; Makhubele, Game; Sedibane, Moditi; Mashinya, Felistas; Mokgotho, Matlou; Matsebatlela, Thabe; Makola, Robert (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
The effect of crude leaf extract of Albizia gummifera (5-160µg/ml) was evaluated on cytotoxic activity against peripheral blood mononuclear and RAW cells stimulated with phorbol myristate acetate (25ng/ml) and formyl peptides (1µM) respectively using the WST-1 technique. Nitric oxide production by RAW cells and Intereukin-2 (IL-2) production by PBMC were also assessed at the same crude leaf extract concentrations (5-160µg/ml) employing colorimetric procedures. The plant leaf extract dose-dependently inhibited growth of mononuclear cells while promoting that of RAW cells (p<0.05). Interleikin-2 production by mononuclear cells and nitric oxide release by RAW cells were inhibited and promoted respectively (p<0.05). Phytochemical studies showed that the leaf extract tested positive for flavonoids, saponins and tannins. This is a preliminary study that showed significant anti- and pro-inflammatory potential at concentration above 20 and 40µg/ml respectively. Further laboratory research is essential to elucidate the anti- and pro-inflammatory biochemical pathways as shown by the in vitro immune-modulatory modalities of this plant species. It is also important to further identify bioactive entities of Albizia gummifera responsible for the observed activities.